2y - 9x = 14 2y = 14 + 9x y = (14 + 9x) / 2
"http://wiki.answers.com/Q/Find_the_equation_of_the_line_perpendicular_to_-9x_2y-3_that_contains_the_poins_3-1"
9x-6y-(12*2y)=0 9x-6y-24y=0 9x-30y=o 9x=30y 3x=10y y=0.3x x=10/3y
What do 6, 9 and 12 have in common? 3. -6y / 3 = -2y +9x / 3 = +3x +12z / 3 = +4z Since they share 3, write 3 outside the brackets, and your solutions inside the brackets: 3(3x-2y+12z)
Substitution is used in Systems of Linear Equations. When you have two equations, such as y=3x+1 and 2y+5=9x+1, then substitution can be used. 2y could be substituted with 2(3x+1). You would have now the equation 6x+2=9x-1, which is more solvable.
2y - 9x = 14 2y = 14 + 9x y = (14 + 9x) / 2
If: 9x-2y = 14 Then: y = 4.5x-7 in slope intercept form
(7x-3y) + (2x+5y) = 9x+2y
-9x + 2y = -69 So 2y = 9x - 69 The other equation can be written as 6x - 4y = 54 or 6x - 2*2y = 54 Substituting for 2y gives 6x - 2*(9x - 69) = 54 6x - 18x + 138 = 54 12x = 84 x = 7 and then 2y = 9x - 69 = 9*7 - 69 = 63-69 = -6 so that y = -3
If you mean: 9x-2y = 7 then it is y = 4.5x-3.5
There is no equation in the question: only an expression. An expression has no answer.
9x + 2y = 5 y - 2x + 3 = 0 Put both equations into the same format. It is often easiest to have just one unknown on (say) the left-hand side of the equation. Let's pick y for this purpose. 2y = -9x + 5 y = 2x - 3 Now make the coeficients of y the same. This can be done by multiplying the 2nd equation by 2. 2y = -9x + 5 2y = 4x - 6 Then, -9x + 5 = 4x - 6 13x = 11 : x = 11/13 And substitue for x in any equation - take the very first original equation. 9x + 2y = 5 99/13 + 2y = 5 : 2y = 5 - 78/13 = - 28/13 y = - 14/13
(1) 9x-2y=73 (2) 5x-9y=9 from (1) 9x-2y+2y=73+2y => 9x= 73+2y => x = (73+2y)/9 put into (2) 5x-9y = 9 => 5(73+2y)/9 - 9y=9 => 10y/9 + 365/9 -9y = 9 => 10y/9 - 9y = 9 -365/9 = -284/9 => -71y/9 = -284/9 => 71y= 284 => y = 284/71 = 4 and x = (73+2*4) / 9 = 9
- x - 2y + 9x - y + 3x = 0 1.) Add like - terms 11x - 3y = 0 x = - 3/11y y = 11/3y
(3x - 2y)(9x^2 + 6xy + 4y^2)
"http://wiki.answers.com/Q/Find_the_equation_of_the_line_perpendicular_to_-9x_2y-3_that_contains_the_poins_3-1"
9x-6y-(12*2y)=0 9x-6y-24y=0 9x-30y=o 9x=30y 3x=10y y=0.3x x=10/3y